Bimbingan Konseling dalam Mengatasi Permasalahan Kehidupan Remaja - Agoestina, Eunike (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2023)
ABSTRACT Adolescents with various problems and issues in their lives require guidance in navigating life and assistance when facing challenges. The problems that occur in adolescent life include family issues, school-related issues, socializing problems, and the use of social media. A counselor needs to provide guidance to adolescents by implementing the following steps: 1) prayer, 2) active listening, 3) applying scriptural principles, 4) guidance through prayer, 5) developing action plans, and 6) providing support. Keywords: counseling, guidance, counselor, counselee